2007
DOI: 10.1021/bm700578z
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Rheology of Surface-Active Biopolymers:  Acacia senegal Gum versus Hydrophobically Modifed Starch

Abstract: Acacia gum is a hybrid polyelectrolyte containing both protein and polysaccharide subunits. We study the interfacial rheology of its adsorption layers at the oil/water interface and compare it with adsorbed layers of hydrophobically modified starch, which for economic and political reasons is often used as a substitute for Acacia gum in technological applications. Both the shear and the dilatational rheological responses of the interfaces are considered. In dilatational experiments, the viscoelastic response o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(73 citation statements)
references
References 48 publications
4
69
0
Order By: Relevance
“…The surface characteristics of BSA solutions at the air-water interface have been studied extensively using multiple techniques, and it is well established that these solutions form rigid viscoelastic interfaces [43,[53][54][55]. On the other hand, although some interfacial studies have been performed on Acacia gum solutions [49,56,57], there is comparatively less literature available for these solutions. Furthermore, there is significant variability present between Acacia gums extracted from different sources.…”
Section: (B) Interfacial Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface characteristics of BSA solutions at the air-water interface have been studied extensively using multiple techniques, and it is well established that these solutions form rigid viscoelastic interfaces [43,[53][54][55]. On the other hand, although some interfacial studies have been performed on Acacia gum solutions [49,56,57], there is comparatively less literature available for these solutions. Furthermore, there is significant variability present between Acacia gums extracted from different sources.…”
Section: (B) Interfacial Dynamicsmentioning
confidence: 99%
“…Testing at frequencies lower than ω = 10 −2 rad s −1 was avoided to prevent evaporation effects from interfering with the measurements. Erni et al [49] have reported that the values of G s and G s measured in a frequency sweep are unchanged upon changing the concentration of Acacia gum in the subphase from 10 wt% to 20 wt%, which has been attributed to the saturation of the interface by Acacia gum molecules. The viscoelastic data obtained from the frequency sweep exhibit a weak power-law behaviour, which is typical of many physical and chemical gels [9] as well as soft glassy materials [13].…”
Section: (B) Interfacial Dynamicsmentioning
confidence: 99%
“…However, drop-drop coalescence in a separation vessel is a dynamic process where droplets undergo shear and compressional deformations 16 . Those deformations and the mobility of stabilizing species are dependent on the drop-drop contact force and droplet interfacial rheology.…”
Section: Introductionmentioning
confidence: 99%
“…lower the viscoelastic moduli) interfacial films under compression 10,12 . However little research has considered the shear rheological properties of interfacial stabilizing films 13 , and only one study has correlated emulsion stability by surface active biopolymers to high shear and compressional elasticity of the interfacial film 16 . The relationship between the demulsifier performance and interfacial rheology has been recognized [20][21][22] , but never investigated systematically for an important class of EO-PO based polymer demulsifiers at toluene-water interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11] Among these studies the adsorption of ␤-lactoglobulin and casein to flat interfaces has been use to better understand the behavior of these proteins in milk emulsions.…”
Section: Introductionmentioning
confidence: 99%